DEVELOPMENT OF 1H-INDAZOLE DERIVATIVES AS ANTI-INFLAMMATORY AGENTS USING COMPUTATIONAL METHODS - NANAWARE, RAJESH B.; CHABUKSWAR, ANURUDDHA R.; ADSULE, PRAJAKTA V.; JAGDALE, SWATI C.; RAUT, KUNAL G. (International Journal of Applied Pharmaceutics, 2024)
Objective: Due to the rising prevalence of disorders linked to inflammation, there is a greater emphasis on the discovery and development of anti-inflammatory drugs, with a focus on producing new structural compounds. Methods: In this research, molecular docking and Molecular Dynamics (MD) simulation study were carried out to evaluate the 1H-indazole analogs as potent anti-inflammatory agents. Results: The compounds containing difluorophenyl, para-toulene and 4-methoxyphenyl group shows significant binding results (9.11, 8.80 and 8.46 kcal/mol respectively) when docked with Cyclooxygenase-2 (COX-2) enzyme 3NT1. The results of the MD simulation indicated that test compound BDF was relatively stable in the COX-2 enzymes active sites. The compound BDF-3NT1 demonstrated substantial affinities for binding with all of its aimed targets following a dynamic Molecular Mechanics with Generalized Born Surface Area (MM-GBSA) analysis. Conclusion: In accordance to this study, newly developed 1H-indazole compounds have the potential for treating inflammation.